Pelatihan Aplikasi Book Creator Sebagai Wadah Membuat Materi Pembelajaran di SMA 03 Maros Sulawesi Selatan: Pelatihan Aplikasi Book Creator Sebagai Wadah Membuat Materi Pembelajaran di SMA 03 Maros Sulawesi Selatan - Nuraeni Nuraeni; Isnaeni Wahab; Zul Astri; Sitti Aisyah; Novalia Tanasy; Nurul Fachrunnisa; Haspia Latauga; Nurul Atira (Pangulu Abdi: Jurnal Pengabdian Kepada Masyarakat, 2023)
The role of applications that were rife after the implementation of distance learning is still being used even though face-to-face has restarted. One application that is creative and can increase student motivation in learning is the use of the Book Creator application. Therefore, teachers will be greatly assisted in making learning materials with this application because it uses the integration of several modes such as images, sound recordings and videos. The purpose of this community service is to provide training to teachers at SMA 3 Maros in operating the Book Creator application. The results obtained from this service are that the trainee teachers show a high interest in this application and provide new insights into making textbooks.